The effect of securities litigation on external financing - Autore, Don M.; Hutton, Irena; Peterson, David R.; Smith, Aimee Hoffmann (Journal of Corporate Finance, 2014)
Using a comprehensive sample of securities litigation, we examine the effect of financial fraud on the subsequent use of external financing. We find that firms with a recent history of securities litigation, particularly more severe litigation, are less likely to seek external debt and equity financing. This negative relationship between prior litigation and external financing is stronger for firms with high information asymmetry. Furthermore, firms significantly reduce their investments in capital expenditures and research and development during the three years following a litigation filing. Thus, the reduction in the availability of external financing due to allegations of financial fraud can have a tangible impact upon the investment opportunities of the firm.